Preparation and study of a radiation-resistant composite material based on V–Ti–Cr and Kh17N2 (ferrite steel 17Cr–12Ni–Fe) - Karakchieva, Natalia I. (Inorganic materials: applied research)
Study of samples of three-layer material “chromium-containing steel Kh17N2/vanadium alloy/chromium-containing steel Kh17N2" obtained by laser growing is presented. The structural-phase state and strength properties of the vanadium alloy and three-layer alloy in the initial state, after heat treatment at 1200°C, and also after irradiation have been studied. The interaction zone of vanadium alloy and steel has been studied in detail.